Catalysts and Deterrents for STEAM Talent Development of Students from Economically-Disadvantaged Families Through Specialized STEAM Talent Residential High Schools. (May 2023) - Kim, Juah; Han, Suksil; Ahn, Doehee; Cho, Seokhee
Talent developmental experiences of economically disadvantaged students of Specialized STEM Talent Residential High Schools (SSTRHS) were investigated. Nine students who were preferentially admitted to SSTRHS due to their families' economic disadvantage were interviewed twice on their experiences from early childhood to college. The data were verified by checking with survey data, national gifted education data and interviews with master teachers. A thematic analysis revealed that STEM talent was recognized early by parents and acknowledged through competitions. However, there were limited resources and opportunities for them to study advanced mathematics systematically and intensely until they entered SSTRHS. At the SSTRHS, they struggled with an extremely accelerated math curriculum. However, with support from advanced peers and teachers, they could cope with their weaknesses caused by limited dosage of STEM learning. Experience conducting research with peers and mentors were the most critical catalysts for their planning for future careers as research scientists.